International terrorism since 1945 series - Martin, Jonathan; Wright, Nicolas ([London] : BBC, 2008)
A 26 series program about the international terrorism that happened began since 1945. Terrorism all over the worl will be discussed in every single cd such as Fatah/Hamas, Al Qaeda, Israel, Taliban and more
Ep. 1. Early Israel terrorism - Ep. 2. Al Qaeda - Ep. 3. The IRA - Ep. 4. Fatah/Hamas - Ep. 5.The PLO - Ep. 6. ETA. Spain - Ep. 7. The Red Brigades - Ep. 8 The Baader-Meinhof Group - Ep. 9. EOKA - Ep. 10. Nasser and Egyptian terrorism - Ep. 11. Colonel Gadaffi and Libya - Ep. 12. Algeria and The AOS - Ep. 13. The SLA and Patty Hearst - Ep. 14. The Weathermen - Ep. 15. The Oklahoma bomber - Ep. 16. The Ku Klux Klan - Ep. 17. The Japanese Sarin Cult - Ep. 18. The Madhi army - Ep. 19. Che Guevara - Ep. 20. Fidel Castro - Ep. 21. Chechen Extremism - Ep. 22. The Taliban - Ep.23. The Taliban - Ep. 24. The Tamil Tigers - Ep. 25. The Moluccan Terroriststs - Ep. 26. The Somali Warlords
narrator : Robert Powell
DVD format
Keywords: Provisional IRA; Irish Republican Army; Terrorism -- Northern Ireland; Northern Ireland -- History -- 20th century